Effect of nanogold particles addition on dimensional stability of complete denture base material: an in - vitro study - Esraa Yousif Taha; Moataz Mostafa Bahgat Elmahdy; Sayed Mohamed Mohamed El Masry; Mohammed Ezzat Elsayed (BMC, 2023)
Abstract Background The most widely used substance in the fabrication of dental prosthesis is poly (methyl methacrylate), or PMMA, and the development of biofilm is frequently associated with its use. To enhance the mechanical properties of heat-polymerized PMMA, this study prepared PMMA/gold nanoparticles (AuNps). The occlusal vertical dimension and tooth movement were examined in the current study. The occlusal vertical dimension was assessed using an electronic digital calliper measuring device, and tooth movement was measured using a CAD Star digital scanner. Results Tooth movement and occlusal vertical dimension of a PMMA/gold nanoparticles (AuNps) were decreased for all groups containing AuNps. Statistical analysis was performed by means of the SPSS 16 software package. Conclusions Incorporation of AuNps into heat- polymerized PMMA resin led to increase dimensional stability of complete denture base material.